2000
DOI: 10.1046/j.1365-2656.2000.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of predation by carabid beetles on slugs

Abstract: Summary1. An explicitly spatial sampling approach was employed to test the null hypothesis that the predation on slugs by the carabid beetle Pterostichus melanarius (Illiger) was opportunistic. 2. The beetles and slugs were sampled across a nested series of grids of sampling points, in a ®eld of winter wheat during June and July 1997. 3. The spatial distribution of all slugs in June was found to change with the scale of the sampling grid, from random on the 0.25 m scale, through aggregation at 1 m, to random a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
162
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 26 publications
(35 reference statements)
5
162
0
Order By: Relevance
“…All but one of the carabid species captured are known to be carnivorous as adults; the exception being Amara obesa, a species that is mainly herbivorous as an adult, and eats grasshopper eggs as a larva (Lindroth 1969). Insects can be regulated by plants (Ayal 1994), and will migrate to areas of high food availability (Bohan et al 2000). Upper elevation sites produced more plant biomass, which possibly provided more food resources for the herbivorous adult A. obesa.…”
Section: Discussionmentioning
confidence: 99%
“…All but one of the carabid species captured are known to be carnivorous as adults; the exception being Amara obesa, a species that is mainly herbivorous as an adult, and eats grasshopper eggs as a larva (Lindroth 1969). Insects can be regulated by plants (Ayal 1994), and will migrate to areas of high food availability (Bohan et al 2000). Upper elevation sites produced more plant biomass, which possibly provided more food resources for the herbivorous adult A. obesa.…”
Section: Discussionmentioning
confidence: 99%
“…A third example may be that of control of field slugs Deroceras reticulatum by carabid beetles in the UK. Bohan et al (2000) found "spatial density dependence" between the slugs and the carabid beetle Pterostichus melanarius, resulting in significant local reductions in slug densities. However, laboratory tests have demonstrated low food quality of these slugs for P. melanarius and other carabid species (Mair & Port, 2001a, b;Fawki et al, 2005).…”
Section: Perspectivesmentioning
confidence: 99%
“…Although P. melanarius is a generalist predator, a reduction in slug population growth rate was observed in field areas with high densities of P. mela narius (Bohan et al, 2000), which further shows that slugs were a single important prey type for P. melanarius. The fact that one type of prey plays a significant role for a generalist predator may be common in agroecosystems, where food diversity for carabid predators appears to be scarce (Van Dijk, 1996).…”
Section: Discussionmentioning
confidence: 85%
“…P. melanarius was detected as a slug predator in the field, using immunological methods (Tod, 1973;Ayre & Port, 1996;Symondson et al, 1996). P. melanarius seems to be a potentially important slug control agent as this bee tle's spatial distribution was found to be significantly associated with slug distribution in winter wheat (Bohan et al, 2000). Moreover Symondson et al (2002) observed a strong relationship between the crop weights of P. melanarius and slug densities over five years, indicating that slugs were a major part of the diet of the beetles.…”
Section: Introductionmentioning
confidence: 99%